Pemutusan Hubungan Diplomatik Kanada Terhadap Iran - Poeteri, Olivia Razmana; Susilo, Djoko; Indriastuti, Suyani (e-SOSPOL (e-ISSN: 2355-1798), 2014)
The severance of diplomatic relations of Canada toward Iran is a Canadian Foreign policy that was taken in order to unilaterally sever the diplomatic relations with Iran. The decision was made as an opposition act to some of Iranâs policies which were considered threatening international security stability that concerned on nuclear development of Iran and to protect the sovereignty of Canadaâs foreign policy in the Middle-East region. The purpose of this study was to determine the factors that caused Canada to sever the diplomatic relations with Iran, using descriptive analysis method. The result showed that the severance of diplomatic relations of Canada with Iran was caused by Iranâs several foreign policies which were in conflict with the foreign policy of Canada such as nuclear development, anti-Israel rhetoric, human rights violations, and support for Bashar AlâAssad regime in the Syrian conflict. Keywords: diplomatic relations, Canada foreign policy, Iran foreign policies